Sodium ion battery negative electrode hard carbon material and preparation method and application thereof

By co-preoxidation and carbonization of the starch raw material of the sodium ion battery negative electrode material and two-stage heat treatment, the problem of starch puffing during the carbonization process is solved, and the performance and production efficiency of hard carbon materials are improved.

CN119430135APending Publication Date: 2025-02-14TONGREN UNIV

Patent Information

Application Number
CN202411579106.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In sodium ion batteries, starch raw materials are prone to puffing during carbonization, resulting in structural damage of hard carbon materials, low carbon rate, low sodium storage capacity and first-time Coulomb efficiency, affecting production efficiency.

Method used

通过对共预氧化原料进行碳化,并与淀粉混合进行两段热处理,包括在空气中和保护性气氛中进行热处理,以协同解决淀粉发泡问题,优化物化结构,提高钠离子的存储容量和传输 way.

Benefits of technology

It effectively inhibits the expansion of starch, improves the performance of hard carbon materials, improves sodium storage capacity and first-time Coulomb efficiency, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430135A_ABST
    Figure CN119430135A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion battery negative electrode hard carbon material and a preparation method and application thereof, and the preparation method comprises the following steps: carbonizing a co-pre-oxidation raw material in an oxygen-containing atmosphere, mixing the carbonized co-pre-oxidation raw material with starch to form a mixed raw material, carrying out first-stage heat treatment in air, and carrying out second-stage heat treatment in a protective atmosphere to obtain the sodium ion battery negative electrode hard carbon material. Wherein the co-pre-oxidation raw material is any one or a mixture of more of biomass and carbonized raw materials. According to the preparation method, the thermal stability of starch pre-carbonization is effectively improved, the effect of inhibiting expansion of starch is achieved, and the problems of low structural damage capacity and the like caused by expansion due to the characteristics of starch raw materials are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion battery preparation, and in particular to a sodium ion battery negative electrode hard carbon material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries dominate the fields of consumer electronics and electric vehicles. However, large-scale energy storage technologies based on lithium have problems such as poor safety, poor low-temperature performance, and high cost. Sodium-ion batteries have similar working principles to lithium-ion batteries. They are both secondary rocking-chair rechargeable batteries. The high abundance of sodium ions and low overall cost have made them a beneficial supplement to the new generation of energy storage technologies. However, due to the essential difference between sodium ions and lithium ions, namely the larger ionic radius of sodium ions and the lower thermodynamic stability of sodium-graphite intercalation, the graphite anode used in lithium-ion batteries cannot be effectively used as a sodium storage anode material. Therefore, it is necessary to develop new sodium storage anode materials for sodium-ion battery technology.

[0003] Hard carbon has the characteristics of disordered internal crystal arrangement and large interlayer spacing, which can store more charge in the same volume and is conducive to Na + The extraction and embedding of hard carbon, and the sources of precursors for synthesizing hard carbon are many and low in cost. It is considered to be a potential negative electrode material for sodium ion batteries and has been widely studied in recent years. However, the complex raw material sources of hard carbon materials have led to the non-fixed process routes, which has restricted the development of sodium ion batteries to a certain extent. Starch is one of the most abundant renewable biomaterials. It has a simple composition, high carbon content and low cost. It is a high-quality precursor for producing hard carbon. However, direct carbonization of starch usually causes swelling, loses its original nearly spherical morphology, and the obtained hard carbon has a large specific surface area, low first coulomb efficiency and low sodium storage capacity, and greatly occupies the production space, reducing production efficiency. It is not conducive to industrial production. When the unstabilized starch is heated to about 300°C, due to the overlapping effects of starch softening and dehydration processes, the starch particles are prone to foaming and melting, thereby forming an extremely fluffy foamed carbon material, which loses its original nearly spherical morphology and greatly occupies the production space. In the past, the method of keeping the temperature at 200-250℃ for more than 20h in air atmosphere was used to promote starch dehydration, so as to ensure that the starch would not foam and expand during high-temperature carbonization. However, this method is too time-consuming and seriously affects industrial production efficiency. The method of adding cross-linking agents, metal oxides, dehydrating agents and oxidants can reduce the time of starch stabilization treatment to a certain extent, but such methods have the problems of high cost, complicated process, and the inability of the substance itself to be carbonized, which is not conducive to the preparation of large-scale starch-based hard carbon.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a method for preparing a hard carbon material for the negative electrode of a sodium ion battery. The method solves the problems of structural destruction, low carbon yield, low capacity, low initial efficiency, etc. caused by expansion due to the characteristics of starch raw materials by carbonizing the co-pre-oxidation raw materials and then superimposing two stages of heat treatment.

[0006] The second object of the present invention is to provide a sodium ion battery negative electrode hard carbon material prepared by the above-mentioned preparation method. The material prepared by the scheme of the present invention has good material performance and is not easy to expand.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The present invention provides a method for preparing a sodium ion battery negative electrode hard carbon material, comprising the following steps:

[0009] The co-preoxidation raw material is first carbonized in an oxygen-containing atmosphere, then mixed with starch to form a mixed raw material, which is subjected to a first stage of heat treatment in air, and then subjected to a second stage of heat treatment in a protective atmosphere, wherein the co-preoxidation raw material is any one or a mixture of biomass and carbonizable raw materials.

[0010] Preferably, the protective atmosphere used is at least one of argon and nitrogen.

[0011] The reason why the co-preoxidation raw materials are first carbonized in the scheme of the present invention is to enhance the oxygen-containing functional groups through carbonization, effectively increase the thermal stability of starch precarbonization and achieve the effect of inhibiting its expansion, thereby solving the problem of low structural destruction capacity caused by expansion due to the characteristics of starch raw materials.

[0012] Next, the starch raw material and the co-preoxidized raw material pre-oxidized in an oxygen-containing atmosphere are mixed and heat-treated in two stages in air and protective atmosphere respectively. This can synergistically solve the starch foaming problem, optimize the physicochemical structure characteristics of starch-based materials, improve the storage capacity and transmission pathway of sodium ions, and prepare high-performance starch-based hard carbon materials.

[0013] The reason why the two-stage heat treatment method can solve the problem of starch foaming is that: the heat treatment process in the air can build a good gas discharge channel inside the starch, which is helpful for the timely discharge of water vapor during the starch carbonization process, avoiding starch gelatinization and inhibiting foaming. Modified starch itself has excellent heat resistance, which can absorb the heat accumulated inside the starch, control the temperature difference between the inside and outside of the starch, avoid local overheating, and produce local foaming. Then heat treatment in a protective atmosphere is because modified starch is rich in oxygen functional groups, which effectively increases the thermal stability of starch. Carbonization in a protective atmosphere isolates oxygen and contributes to the stability of the carbon spherical structure. Therefore, the combination of the two-stage heat treatment method finally achieves the effect of inhibiting starch foaming and increasing stability.

[0014] The starch raw material and the co-preoxidation raw material can be mixed based on known processes such as stirring, grinding, ultrasonic dispersion, ball milling, etc.

[0015] Preferably, the carbonization temperature is 190 to 300°C, preferably 220 to 300°C;

[0016] Preferably, the heating rate of the carbonization is 1-10°C / min.

[0017] The reason for pre-oxidation is to carbonize the co-pre-oxidized raw materials. The thermal decomposition temperature of starch is between 200 and 220°C. If the temperature is too low, the pre-oxidation will be incomplete, and if the temperature is too high, the starch inhibition strategy will fail. Therefore, it is necessary to control it within the appropriate temperature range.

[0018] Preferably, the temperature of the first heat treatment is 180-250°C, preferably 200-230°C;

[0019] Preferably, the first heat treatment lasts for 2 to 10 hours, preferably 4 to 6 hours;

[0020] Preferably, the heating rate of the first heat treatment is 1-10°C / min

[0021] The second heat treatment is divided into two stages. The temperature of the first stage is 700°C to 850°C, the holding time is 1 to 5 hours, and the heating rate is 1 to 10°C / min.

[0022] The temperature of the second stage is 1300°C ~ 1400°C, and the insulation time is 2 ~ 10 hours.

[0023] The reason why the second heat treatment is carried out in two stages is that the temperature of the first stage achieves the purpose of removing tar, so that the structure is more stable under the subsequent temperature operation of the second stage.

[0024] The above temperatures are all designed to synergistically solve the starch foaming problem, because only when the temperature of the first stage reaches the purpose of removing tar can the structure be guaranteed to be more stable at the temperature of the subsequent second stage. Therefore, the temperature and time parameters of the two stages need to be controlled within an appropriate range.

[0025] Preferably, the co-pre-oxidation raw materials include at least one of oxidized starch, hydroxypropyl starch, bamboo powder, and hydrothermally treated starch. The co-pre-oxidation of the same starch material ensures the uniformity and stability of the final material, can optimize the physicochemical structure characteristics of starch-based materials, improve the storage capacity and transmission pathway of sodium ions, reduce the heat treatment time and optimize the cost, and can prepare high-performance starch-based hard carbon materials.

[0026] Preferably, the content of the co-preoxidation raw material in the mixed raw material is 10 to 50 wt%, preferably 10 to 30 wt%.

[0027] Preferably, the oxygen content in the oxygen-containing atmosphere is above 10v%, and preferably contains at least one of oxygen, air, a mixture of oxygen-diluent, and a mixture of air-diluent;

[0028] Preferably, the diluent gas includes at least one of nitrogen and an inert gas.

[0029] Preferably, the starch raw material in the mixed raw material includes one or more of corn starch, tapioca starch, potato starch, rice starch, wheat starch and mung bean starch.

[0030] The present invention also provides a sodium ion battery negative electrode hard carbon material prepared by the above preparation method;

[0031] Preferably, in the negative electrode hard carbon material, the content of the starch-based negative electrode active material is above 50 wt %, more preferably, the content of the negative electrode active material is above 60 wt %, further ranging from 70 to 90 wt %.

[0032] The sodium ion battery negative electrode hard carbon material prepared by the above preparation method of the present invention has good application in equipment driving.

[0033] The scheme of the present invention is based on the above-mentioned method of adding co-pre-oxidation raw material carbonization + three-stage heat treatment, which can solve the foaming problem faced by the heat treatment of starch raw materials. In addition, it can also optimize the physical and chemical structure, improve the starch-based hard carbon capacity and first effect, and has better technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] By reading the detailed description of the preferred embodiment below, various other advantages and benefits will become clear to those of ordinary skill in the art. The accompanying drawings are only used for the purpose of illustrating the preferred embodiment and are not considered to be limitations of the present invention. In addition, the same reference symbols are used to represent the same components throughout the accompanying drawings.

[0035] Figure 1 This is a photo of the hydroxypropyl starch in Example 1 after pre-oxidation at 230°C;

[0036] Figure 2 This is a scanning electron microscope image of the hard carbon prepared by doping with hydroxypropyl starch in Example 1;

[0037] Figure 3 This is a photo of the hydroxypropyl starch after pre-oxidation at 230°C in Example 3;

[0038] Figure 4 This is a photo of starch pre-oxidized at 230°C in Comparative Example 1 of the present invention;

[0039] Figure 5 This is a scanning electron microscope image of the hard carbon prepared by sintering corn starch in Comparative Example 1. DETAILED DESCRIPTION

[0040] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0041] Example 1

[0042] Step (1): Carbonization of the co-pre-oxide

[0043] The hydroxypropyl starch was sieved through 200 mesh, and the temperature was raised to 230° C. at a heating rate of 2° C. / min in a muffle furnace in an air atmosphere, and kept at this temperature for 5 h. The resultant was ground and sieved through 200 mesh.

[0044] Step (2): First heat treatment

[0045] The heat-treated hydroxypropyl starch and corn starch were mixed in a mass ratio of 1:9 and added to a stirring device for uniform stirring to obtain a premix. The premix was placed in a low-temperature sintering furnace, heated to 230°C (marked as T1) in an air (oxygen-containing atmosphere) environment, with a heating rate of 2°C / min and a holding time of 6h. After the holding period, a preoxidized mixture (first-stage material) was obtained. The specific results are shown in Figure 1 .

[0046] Step (3): Second stage heat treatment

[0047] The first-stage material is placed in a high-temperature sintering furnace, ultrapure argon is introduced, and the temperature is raised to 800°C (marked as T2) at a heating rate of 5°C / min and a holding time of 2h. After the holding period is completed, the second-stage material is obtained.

[0048] Step (4): Third stage heat treatment

[0049] After step 2, the second stage material was heated to 1300°C (marked as T3) at a rate of 5°C / min and kept at this temperature for 2h and then cooled to room temperature. The material was ground and dispersed after the cooling rate was 2°C / min to obtain a hard carbon negative electrode material, and its SEM spectrum is shown in Figure 2 .

[0050] Example 2

[0051] Step (1): Heat treatment of the co-pre-oxide

[0052] The oxidized starch was sieved through 200 mesh, heated to 190° C. at a rate of 1° C. / min in a muffle furnace in an air atmosphere, kept at this temperature for 10 h, and the resultant was ground and sieved through 200 mesh.

[0053] Step (2): First heat treatment

[0054] The heat-treated oxidized starch and corn starch were mixed in a mass ratio of 1:9 and added to a stirring device for uniform stirring to obtain a premix. The premix was placed in a low-temperature sintering furnace, heated to 180°C (marked as T1) in an air (oxygen-containing atmosphere) environment, with a heating rate of 1°C / min and a holding time of 4h. After the holding was completed, a preoxidized mixture (a first-stage material) was obtained.

[0055] Step (3): Second stage heat treatment

[0056] The pre-oxidized mixture was placed in a high-temperature sintering furnace, ultrapure argon was introduced, the temperature was raised to 850°C (marked as T2), the heating rate was 10°C / min, the insulation time was 1h, and the second-stage material was obtained after the insulation was completed.

[0057] Step (4): Third stage heat treatment

[0058] After step 2, the temperature was raised to 1350°C (marked as T3) at a rate of 5°C / min and kept at this temperature for 10 hours and then cooled to room temperature. After the temperature was lowered at a rate of 2°C / min, the material was ground and dispersed to obtain a hard carbon negative electrode material.

[0059] Example 3

[0060] Step (1): Heat treatment of the co-pre-oxide

[0061] The hydroxypropyl starch was sieved through 200 mesh, and the temperature was increased to 300° C. at a rate of 10° C. / min in a muffle furnace in an air atmosphere, and the temperature was kept for 2 h. The resultant was ground and sieved through 200 mesh.

[0062] Step (2): First heat treatment

[0063] The heat-treated hydroxypropyl starch and potato starch were mixed in a mass ratio of 1:9 and added to a stirring device for uniform stirring to obtain a premix. The premix was placed in a low-temperature sintering furnace, heated to 250°C (marked as T1) in an air (oxygen-containing atmosphere) environment, with a heating rate of 10°C / min and a holding time of 10h. After the holding period, a preoxidized mixture (first-stage material) was obtained. The specific results are shown in Figure 3 .

[0064] Step (2): Second stage heat treatment

[0065] The pre-oxidized mixture was placed in a high-temperature sintering furnace, ultrapure argon was introduced, the temperature was raised to 700°C (marked as T2), the heating rate was 1°C / min, the insulation time was 5h, and the second-stage material was obtained after the insulation was completed.

[0066] Step (3): Third stage heat treatment

[0067] After step 2, the temperature was raised to 1400°C (marked as T3) at a rate of 5°C / min and kept at this temperature for 5h, and then cooled to room temperature. After the temperature was lowered at a rate of 2°C / min, the material was ground and dispersed to obtain a hard carbon negative electrode material.

[0068] Comparative Example 1

[0069] Step (1): Pre-carbonization

[0070] The corn starch was placed in a muffle furnace and heated to 230°C (marked as T1), with a heating rate of 2°C / min and a holding time of 6h. After the holding time was completed, a pre-oxidation product was obtained. Figure 4 It is known that under this condition, the expansion of the oxidation products is very serious.

[0071] Step (2): Second stage heat treatment

[0072] The pre-oxidation product was placed in a tubular furnace, ultrapure argon was introduced, the temperature was raised to 800°C (marked as T2), the heating rate was 5°C / min, the insulation time was 2h, and the second stage material was obtained after the insulation was completed.

[0073] Step (3): Third stage heat treatment

[0074] After step 2, the temperature was raised to 1300°C (marked as T3) at a rate of 5°C / min and kept at this temperature for 2h and then cooled to room temperature. The material was ground and dispersed after the cooling rate was 2°C / min to obtain a hard carbon negative electrode material, the SEM image of which is shown in Figure 5.

[0075] Comparative Example 2

[0076] Step (1): Co-precarbonization

[0077] The corn starch and hydroxypropyl starch were mixed and placed in a muffle furnace and heated to 230°C (marked as T1) at a heating rate of 2°C / min and a holding time of 6h. After the holding period, a pre-oxidation product was obtained.

[0078] Step (2): Second stage heat treatment

[0079] The pre-oxidation product was placed in a tubular furnace, ultrapure argon was introduced, the temperature was raised to 800°C (marked as T2), the heating rate was 5°C / min, the insulation time was 2h, and the second stage material was obtained after the insulation was completed.

[0080] Step (3): Third stage heat treatment

[0081] After step 2, the temperature was raised to 1300°C (marked as T3) at a rate of 5°C / min and kept at this temperature for 2h and then cooled to room temperature. After the temperature was lowered at a rate of 2°C / min, the material was ground and dispersed to obtain a hard carbon negative electrode material.

[0082] Comparative Example 3

[0083] Step (1): Heat treatment of the co-pre-oxide

[0084] The hydroxypropyl starch was sieved through 200 mesh, and the temperature was raised to 230° C. at a heating rate of 2° C. / min in a muffle furnace in an air atmosphere, and kept at this temperature for 5 h. The resultant was ground and sieved through 200 mesh.

[0085] Step (2): First heat treatment

[0086] The heat-treated mixture is mixed with corn starch in a mass ratio of 1:9 and added to a stirring device for uniform stirring to obtain a premix. The premix is ​​placed in a low-temperature sintering furnace, heated to 230°C (marked as T1) in an air (oxygen-containing atmosphere) environment, with a heating rate of 2°C / min and a holding time of 6 hours. After the holding is completed, a preoxidized mixture (a first-stage material) is obtained.

[0087] Step (3): Second stage heat treatment

[0088] The temperature was raised to 1300°C (marked as T3) at a rate of 5°C / min and kept at this temperature for 2h and then cooled to room temperature. After the temperature was lowered at a rate of 2°C / min, the material was ground and dispersed to obtain a hard carbon negative electrode material.

[0089] Experimental Example 1

[0090] Electrochemical testing:

[0091] The prepared hard carbon negative electrode material (materials prepared in Example 1 and Comparative Examples 1-3), conductive carbon (super-p), and sodium carboxymethyl cellulose (CMC) are dissolved in deionized water at a mass ratio of 9:0.5:0.5 to prepare a uniform slurry, and the slurry is evenly coated on the aluminum foil current collector, and then placed in a drying oven at 120°C and dried for 12 hours to obtain a hard carbon electrode sheet.

[0092] The hard carbon electrode is punched into a 10 mm diameter electrode, with the sodium metal sheet as the negative electrode side and the hard carbon electrode as the positive electrode side. The electrolyte is 1M NaPF 6 in DEC:EC=1:1Vol%, CR2025 button cells were assembled in a glove box filled with argon atmosphere. The battery was tested for electrochemical performance, with a current density of 30mA / g and a voltage range of 0.01-3V. Table 1 shows the electrochemical performance parameters of hard carbon synthesized under different conditions. It can be seen from Table 1 that the reversible capacity and first charge and discharge efficiency of the hard carbon prepared after adding hydroxypropyl starch have been greatly improved, and the carbon yield has also been improved. Since no co-pre-oxidation raw materials were added in Comparative Example 1, and no co-pre-oxidation raw materials were carbonized in Comparative Example 2, and only one stage of treatment was performed in the second heat treatment stage after Comparative Example 3, the effects could not reach the expected results.

[0093] Table 1 Comparison of electrochemical parameters of hard carbon synthesized in Examples and Comparative Examples

[0094]

[0095] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.

Claims

1. A method for preparing a sodium ion battery, characterized in that: The steps include: The positive electrode layered oxide material and LALZO are mixed, alcohol is added, stirred, and sintered at high temperature to obtain a positive electrode layered oxide material for a sodium ion battery coated with LALZO; The high temperature sintering step includes sintering at a temperature of 200° C.-400° C. for 2 h-6 h, and then sintering at a temperature of 550° C.-850° C. for 1 h-8 h.

2. The preparation method according to claim 1, characterized in that: The alcohol includes at least one of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, isobutanol, sec-butanol, tert-butanol, n-pentanol, sec-pentanol, n-octanol, sec-octanol and n-hexanol.

3. The preparation method according to claim 1, characterized in that: The high temperature sintering step includes: sintering at a temperature of 250° C.-350° C. for 3 h-4 h, and then sintering at a temperature of 600° C.-700° C. for 2 h-6 h.

4. The preparation method according to claim 1, characterized in that: The amount of LALZO used is 0.1%-3% by weight of the positive electrode layered oxide material, preferably 0.5%-2.5%, and more preferably 1-2%.

5. The preparation method according to claim 1, characterized in that: After mixing, grinding is performed, and the grinding time is 20-60 minutes.

6. The preparation method according to claim 1, characterized in that: After grinding, add alcohol and stir for 10-40 minutes.

7. The preparation method according to claim 1, characterized in that: After high temperature sintering, the temperature is cooled at a rate of 0.5°C / min-1°C / min.

8. A sodium ion battery prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the sodium ion battery prepared by the preparation method according to any one of claims 1 to 7 and the sodium ion battery according to claim 8 in device driving.

Citation Information

Patent Citations

  • Starch-based hard carbon sodium ion battery negative electrode material as well as preparation method and application thereof

    CN116544386A

  • Biomass-starch composite-based hard carbon material, preparation thereof and application of biomass-starch composite-based hard carbon material in sodium-ion battery

    CN117163941A

  • Starch-based hard carbon material as well as preparation method and application thereof

    CN118324118A

  • Starch-based hard carbon negative electrode active material, preparation thereof and application of starch-based hard carbon negative electrode active material in sodium-ion battery

    CN118458748A

  • Preparation method for hard carbon negative electrode material, and use of preparation method

    WO2024000817A1

Cited By

  • Sodium-ion battery hard carbon material and preparation method thereof

    CN122380342A